2019
DOI: 10.3390/w11071399
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and Floods—A Global Review

Abstract: There is a strong inter-annual and inter-decadal variability in time series of flood-related variables, such as intense precipitation, high river discharge, flood magnitude, and flood loss at a range of spatial scales. Perhaps part of this variability is random or chaotic, but it is quite natural to seek driving factors, in a statistical sense. It is likely that climate variability (atmosphere–ocean oscillation) track plays an important role in the interpretation of the variability of flood-related characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 117 publications
1
55
0
Order By: Relevance
“…This agrees well with Archfield et al (2016), where climate indices (Pacific Decadal Oscillation, North Atlantic Oscillation, and Atlantic Multi‐decadal Oscillation) did not show widespread and strong correlations with floods (aside from New England) based on 345 streamflow stations across the USA. Nevertheless, Kundzewicz et al (2019) emphasized that random component of climate variability as well as the variability of flood‐related variables is strong. As global temperature rises, ocean‐atmospheric oscillations and climatic variability could intensify and their impacts could become more pronounced and detectable in hydroclimatic time series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees well with Archfield et al (2016), where climate indices (Pacific Decadal Oscillation, North Atlantic Oscillation, and Atlantic Multi‐decadal Oscillation) did not show widespread and strong correlations with floods (aside from New England) based on 345 streamflow stations across the USA. Nevertheless, Kundzewicz et al (2019) emphasized that random component of climate variability as well as the variability of flood‐related variables is strong. As global temperature rises, ocean‐atmospheric oscillations and climatic variability could intensify and their impacts could become more pronounced and detectable in hydroclimatic time series.…”
Section: Discussionmentioning
confidence: 99%
“…River hydrology responds directly to these variations. Quasiperiodic climate variability may also affect river water abundance through ocean‐atmospheric oscillations ranging from several years to several decades (Kundzewicz et al, 2019). El Niño Southern Oscillation (ENSO) is the most dominant feature of quasiperiodic ocean–atmosphere oscillations, preceded only by seasonal cycle (Glantz, 1996), and have the greatest effects on worldwide climate (Yeh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Unpredictable rainfall behavior over complex urban systems and changing environments may cause an increased risk of flooding. Previous studies have suggested that the frequency of extreme, short duration rainfall events is increasing, such that there may be a higher chance of increased magnitudes and frequencies of flooding [1,3]. Projection reports also suggest that flood frequency may increase, especially over southeast Asia [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…All these modes are of considerable and broad interest, also in climate impact studies related to teleconnections, i.e., relationships between climate variations in places located far away from each other. For example, Kundzewicz et al [1,2] analyzed links of indices of oscillation in the ocean-atmosphere system with abundance of water (intense precipitation, high river discharge, floods), while Kundzewicz et al [3] studied links with global annual temperature and Norel et al [4] examined relationships with river runoff using machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper deals with a subset of the above oscillation modes. We discuss indices of ENSO, the NAO, the PDO, and the AMO that have been found important in studies of links between abundance of water (intense precipitation and floods) and climate variability as well as global annual temperature [1,3].…”
Section: Introductionmentioning
confidence: 99%